Terms of engagement : changing the way we change organizations - Axelrod, Richard H. (Berrett-Koehler Pub. San FranciscoUS, 2000)
Presents the engagement paradigm as a viable alternative to the old change management paradigm. Explores 4 principles for producing an engaged organization, namely: widening the circle of involvement; connecting people to each other and ideas; creating communities for action; and, embracing democracy.